The Interactional Approach to The Teaching Of Writing and Its Implications for Second Language Acquisition - Lies Amin Lestari (TEFLIN, 2006)
Writing is a language skill which is relatively difficult to acquire. A number of efforts have been made to develop the studentsÃ¢â¬â¢ writing skill, among others is by applying different approaches to the teaching of writing. This article discusses the interactional approach to the teaching of writing and its implications for second language acquisition.